Postoperative Radiotherapy for pT1- and pT2-Classified Squamous Cell Carcinoma of the External Auditory Canal - Nabuurs, Cindy H; Kievit, Wietske; Leemans, Charles René Reinier; Smit, Conrad F G M; van den Brekel, Michiel W M; Pauw, Robert J; van der Laan, Bernard F A M; Jansen, Jeroen C; Lacko, Martin; Braunius, Weibel W; Dai, Chunfu; Shi, Xunbei; et al. (Cancers, 2024)
BACKGROUND: There is no consensus regarding the indication for postoperative radiotherapy (PORT) for T1- and T2-classified squamous cell carcinoma (SCC) of the external auditory canal (EAC) even with negative surgical margins. This study aimed to evaluate whether PORT provides additional benefits for these cases. METHODS: We collected retrospective data from fourteen international hospitals, including resected pT1- and pT2-classified EAC SCC with negative surgical margins. RESULTS: A total of 112 early-stage radically resected EAC SCC were included, with 48 patients receiving PORT. The 5-year DFS of T1- and T2-classified EAC SCC treated with PORT was not statistically significantly different (92.9% and 76.9%, respectively) compared to the group treated without PORT (100% and 90.9%, respectively; p-values of 0.999 and 0.526, respectively). EAC SCC treated with PORT more frequently exhibited perineural and angioinvasive growth. Eighteen patients experienced side effects related to radiotherapy, of which one patient developed osteoradionecrosis. CONCLUSIONS: Our study suggests that PORT for early-stage radically resected EAC SCC should only be considered in selected cases with perineural, infiltrative growth or angioinvasive growth, and with a close margin. This approach helps mitigate the negative impact on quality of life and the risk of side effects associated with radiotherapy.